2013
DOI: 10.1074/jbc.m113.484279
|View full text |Cite
|
Sign up to set email alerts
|

A Crayfish Insulin-like-binding Protein

Abstract: Background:In Crustacea, a male-specific insulin-like androgenic hormone governs sexual differentiation. Results: A crayfish insulin-like growth factor-binding protein (Cq-IGFBP) was expressed and found to bind the androgenic hormone. Conclusion: Cq-IGFBP is part of the scheme modulating the crustacean androgenic hormone. Significance: Cq-IGFBP is the first IGFBP found that interacts with an insulin-like gender-specific ligand linking early evolution of insulin pathways with gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 54 publications
(66 reference statements)
1
25
0
Order By: Relevance
“…The interaction between crustacean IGFBP and IAG was first demonstrated in C. quadricarinatus (Rosen et al, 2013). In this study, we verified the interaction between EsIGFBP7 and EsIAG using a yeast-two hybrid assay.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The interaction between crustacean IGFBP and IAG was first demonstrated in C. quadricarinatus (Rosen et al, 2013). In this study, we verified the interaction between EsIGFBP7 and EsIAG using a yeast-two hybrid assay.…”
Section: Discussionsupporting
confidence: 56%
“…Although the IGFBP family has many members in vertebrates, only one member has been identified in crustacean species, until now (Rosen et al, 2013;Li et al, 2015). Crustacean IGFBPs are most homologous with vertebrate IGFBP7, and they share a common structural organization of an IB domain in the N-terminus, a KAZAL domain in the middle, and an IG domain in the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IAG is known to regulate male sexual development, specifically secondary sexual features and spermatogenesis, suggesting that the levels of IAG expression in the AG and of the hemolymph IAG titers may be closely associated with male sexual maturity. It is reported that IAG requires a binding partner, an insulin-like binding protein, or an insulin-like binding protein like peptide [ 24 ]. The exact mode of the IAG mechanism by which it regulates such processes still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…The same species of diatoms were tested in other times [15] or on other decapods [25] but they did not elicit any bioactivity comparable to the one detected on young post-larvae of H. inermis . Additionally, toxicity tests performed with crude extracts of the diatom C. scutellum parva on embryos of the sea urchin Paracentrotus lividus did not elicit any significant effects [26].…”
Section: Introductionmentioning
confidence: 99%